Ribosome profiling in plants: what is not lost in translation?. (27th May 2020) - Kage, Udaykumar; Powell, Jonathan J; Gardiner, Donald M; Kazan, Kemal
Abstract : Translation is a highly complex process, and better understanding of how it is regulated in plants is important. Ribosome profiling provides unprecedented new insights into key processes involved in translational control. Abstract: Translation is a highly dynamic cellular process whereby genetic information residing in an mRNA molecule is converted into a protein that in turn executes specific functions. However, pre-synthesized mRNA levels do not always correlate with corresponding protein levels, suggesting that translational control plays an essential role in gene regulation. A better understanding of how gene expression is regulated during translation will enable the discovery of new genes and mechanisms that control important traits in plants. Therefore, in recent years, several methods have been developed to analyse the translatome; that is, all mRNAs being actively translated at a given time, tissue, and/or developmental stage. Ribosome profiling or ribo-seq is one such technology revolutionizing our ability to analyse the translatome and in turn understand translational control of gene expression. Ribo-seq involves isolating mRNA–ribosome complexes, treating them with a RNase, and then identifying ribosome-protected mRNA regions by deep sequencing. Here, we briefly review recent ribosome profiling studies that revealed new insights into plant biology. Manipulation of novel genes identified using ribosome profiling could prove useful for increasing yield through improved biotic and abiotic stress tolerance.